2018
DOI: 10.1111/and.13133
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect of progesterone on motility and velocity of fresh, vitrified without permeable cryoprotectants and frozen with permeable cryoprotectants human spermatozoa

Abstract: Steroid hormone progesterone has been found to play an important role in the migration of spermatozoa through the reproductive tract, as well as to induce hyperactive motility and increase sperm velocity. The aim of this study was to examine whether progesterone could induce beneficial effects in vitrified and slow-frozen spermatozoa. During the research process, 50 semen samples were divided into three treatment groups; noncryopreserved, slow-freezing and vitrification. After thawing and an incubation period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The study by Sayme et al (6) showed that P4 increased hyperactivated motility in human sperm cryopreserved by slow freezing and vitrification, at P4 concentrations of 0, 25, 50 nM. The present study was different from that of Sayme et al (6) in that our study used fresh human sperm.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…The study by Sayme et al (6) showed that P4 increased hyperactivated motility in human sperm cryopreserved by slow freezing and vitrification, at P4 concentrations of 0, 25, 50 nM. The present study was different from that of Sayme et al (6) in that our study used fresh human sperm.…”
Section: Introductionmentioning
confidence: 59%
“…The study by Sayme et al (6) showed that P4 increased hyperactivated motility in human sperm cryopreserved by slow freezing and vitrification, at P4 concentrations of 0, 25, 50 nM. The present study was different from that of Sayme et al (6) in that our study used fresh human sperm. The aim of the present study was to evaluate the effect of various P4 concentrations on hyperactivated motility and membrane integrity of fresh human sperm.…”
Section: Introductionmentioning
confidence: 59%
“…Exposure of boar sperm to P4 concentrations ranging from 10 to 100 nM was reported to rapidly enhance sperm viability and sperm glucose and lipid metabolism compared with untreated controls [ 128 ]. In addition, P4 at 50 nM was found to stimulate within 30 min the progressive motility of human sperm after cryopreservation [ 140 ], suggesting a significant role of P4 on sperm motility. Accordingly, sperm hyperactivated motility was shown to be promoted by nanomolar concentrations of P4 in cattle [ 105 ] and hamster [ 141 ].…”
Section: Steroid Hormones Locally Regulate Sperm Migration Capacitation and Release From The Oviduct Reservoirmentioning
confidence: 99%
“…(A) Treatment with picomolar concentrations of E2 inhibits sperm motility in sheep [ 129 ], promotes capacitation in mice [ 132 ], and acrosome reaction in sheep [ 129 ]. (B) Nanomolar concentrations of P4 found after ovulation have beneficial effect on sperm capacitation in pigs [ 4 , 128 , 142 , 145 ], human [ 140 , 143 , 144 , 148 ], cattle [ 105 ], sheep [ 129 ], in horse [ 129 ], in macaques [ 147 ], and in hamster [ 141 ]. (C) A suppressive effect of picomolar levels of E2 on P4-induced hyperactivation was reported in hamster [ 149 , 150 ] and humans [ 148 ].…”
Section: Steroid Hormones Locally Regulate Sperm Migration Capacitation and Release From The Oviduct Reservoirmentioning
confidence: 99%